Securing multimodal biometric template using local random projection and homomorphic encryption. (November 2022) - Vallabhadas, Dilip Kumar; Sandhya, Mulagala
Abstract: Due to the rapid advancement of technology, biometrics is widely used in authenticating a person. The primary issue in biometric authentication is template protection, which protects the user's privacy. To achieve this level of security, we transform the original template generated from the extracted features into a pseudo template. This paper considers two biometric traits, namely Iris and Fingerprint. First, the features are extracted from both the traits. After extracting the features, the feature vectors are compressed to reduce the size. Then the feature vectors of both the traits are fused. Later, local random projection (LRP) is applied to this template to build a revocable and un-linkable template. Finally, fully homomorphic encryption (FHE) is applied to this generated template to secure the user's privacy, as all operations on the template are carried on encrypted data. Our proposed method improves the accuracy of the system as it generates rotational invariant codes. This proposed method is tested on the Children Multimodal Biometric Database (CMBD), which shows that our method can maintain user privacy with a good accuracy rate. Our method achieves an EER of 0.0214%.